2012
DOI: 10.1371/journal.pone.0036554
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and Analysis of the Mediterranean Amphioxus (Branchiostoma lanceolatum) Transcriptome

Abstract: BackgroundThe basally divergent phylogenetic position of amphioxus (Cephalochordata), as well as its conserved morphology, development and genetics, make it the best proxy for the chordate ancestor. Particularly, studies using the amphioxus model help our understanding of vertebrate evolution and development. Thus, interest for the amphioxus model led to the characterization of both the transcriptome and complete genome sequence of the American species, Branchiostoma floridae. However, recent technical improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…When B. floridae orthologs had not been previously characterized in the extensive phylogenetic analyses of Kerner et al (2011), we identified putative stem cell markers using BLASTp searches against the genomes of B. floridae and B. belcheri, and confirmed the identity of our B. lanceolatum proteins by comparison with published sequences in other cephalochordates (Supplementary File 4), including transcriptomic data from B. lanceolatum in the NCBI TSA database (Oulion et al, 2012). We generated phylogenies that include, where possible, sequences from more than one amphioxus species to support the identity of these proteins (Supplementary File 5; and see below).…”
Section: Identification Of Candidate Germline and Somatic Stem Cell Mmentioning
confidence: 57%
“…When B. floridae orthologs had not been previously characterized in the extensive phylogenetic analyses of Kerner et al (2011), we identified putative stem cell markers using BLASTp searches against the genomes of B. floridae and B. belcheri, and confirmed the identity of our B. lanceolatum proteins by comparison with published sequences in other cephalochordates (Supplementary File 4), including transcriptomic data from B. lanceolatum in the NCBI TSA database (Oulion et al, 2012). We generated phylogenies that include, where possible, sequences from more than one amphioxus species to support the identity of these proteins (Supplementary File 5; and see below).…”
Section: Identification Of Candidate Germline and Somatic Stem Cell Mmentioning
confidence: 57%
“…An amphioxus (B. lanceolatum) Prdm12 cDNA was amplified by PCR from cDNA generated from total RNA from adults, using primers forward 5′-ATGA-AGCCGACCCTGTTTGATC-3′ and reverse 5′-ACATGGCGACCGAA-CGAACGTC-3′ (Oulion et al, 2012). …”
Section: Prdm12 Cdnas and Expression Constructsmentioning
confidence: 99%
“…lanceolatum Fox sequences were recovered from its reference transcriptome (Oulion et al, 2012) by TBLASTN using sequences from B. floridae as queries. Specific primers were then designed for RT-PCR amplification from total RNA.…”
Section: Cloning and Expression Studymentioning
confidence: 99%
“…We looked for Fox gene sequences in the reference transcriptome of B. lanceolatum (Oulion et al, 2012). The sequences that were recovered were used to conduct a phylogenetic tree reconstruction presented in Figure 1.…”
Section: Molecular Phylogenetic Analysis Of B Lanceolatum Fox Gene Smentioning
confidence: 99%
See 1 more Smart Citation